Using an integrated model of the theory of planned behavior and the temporal self-regulation theory to explain physical activity in patients with coronary heart disease - Wang, Wenqin; Wu, Minjuan; Hua, Yun; Zhang, Xingwei; Feng, Guohe (Frontiers in Psychology, 2023)
Background This study aimed to explore the psychosocial determinants of the physical activity (PA) levels in patients with coronary heart disease (CHD) using an integrated theoretical model based on the theory of planned behavior (TPB) and the temporal self-regulation theory (TST). Method This was a prospective study conducted at the Affiliated Hospital of Hangzhou Normal University, Zhejiang, China. A total of 279 patients with CHD [176 men aged 26–89 years, mean (M) = 64.69, standard deviation (SD) = 13.17] were selected under the study inclusion criteria by convenience sampling. The data on attitude, subjective norm (SN), perceived behavioral control (PBC), and intention variables for the TPB model and consideration of future consequences (CFC), habit, and self-control (SC) variables for the TST model were collected 1–2 days before the discharge (Time 1, T1) of the participants, and a telephone follow-up was made to assess the participants' self-reported PA levels 1 week after their discharge (Time 2, T2). Results The results revealed that only 39.8% of the patients with CHD met the guidelines' recommendations on PA. The data analyses using structural equation modeling (SEM) in the Mplus 8.3 modeling program showed that, in the simple mediation model, attitude, PBC, and CFC were positively related to the intention to practice guideline-recommended levels of PA but SN was not. In addition, intention was shown to mediate the relationships between attitude, PBC, CFC, and PA levels. Furthermore, based on the moderated mediating model, intention and habit were shown to be positively associated with PA levels but SC was not. Moreover, SC played a significant moderating role between intention and PA levels. However, habit strength did not moderate the relationship between intention and PA levels. Conclusion An integration of the TPB and TST models offers a good theoretical tool for understanding PA levels in patients with CHD.